Orędzie biskupów polskich w ocenie niemieckiego MSZ - Madajczyk, Piotr (Rocznik Polsko-Niemiecki, 2011)
The history of the Polish Bishops’ Letter of Reconciliation to the German bishops, sent in the autumn of 1965, that is, in a very inopportune political climate, is now relatively well known and researched. What contributed to its being widespread, was the perception of it as a pre-cursor of the Polish-German reconciliation, an initiative which, while not capable of having a real impact on Poland and West Germany in the 60s, pointed to alternative methods by which it could be carried out and distanced itself from retaining hostility as a basis for Polish-German relations and using the stereotype of a threat on the part of Germany in Polish domestic politics. The circumstances in which the Letter had been brought into being could be studied thanks to the opening of Polish archives after the fall of Communism. The article shows how the Letter was received by West German diplomacy, in terms, most of all, of an appraisal of the chances and opportunities in the international arena which could follow from such a reception. What was important from Bonn’s point of view was the setting of the controversies around the Letter in Poland in a wider context, namely, one of balancing the relationships between determinants rooted in domestic politics, the policy of Moscow and the East Block and that of the Vatican.